Effect of Phoenix dactylifera pollen grain on maturation of preantral follicles in NMRI mice - Salek Abdollahi Farzaneh; Baharara Javad; Nejad-Shahrokhabadi Khadijeh; Namvar Farideh; Amini Elaheh (Shahrekord University of Medical Sciences, 2015)
Introduction: Optimizing an ideal culture system that is comparable to follicle environment to obtain mature oocytes is one of the important criteria in in vitro maturation (IVM). Phoenix dactylifera L. commonly known as date palm is an important herb in Asia folk medicine that is used to improve fertility in women from ancient time. The aim of this study was to investigate the effect of date palm pollen grain extract on IVM of mouse follicles. Methods: In this study follicles with 1 or 2 layers of granulosa cells and round oocytes were isolated from 2-3 weeks old female NMRI mice ovaries. Follicles were cultured in IVM media with different concentrations 0, 10, 20, 30, 40 μg/ml of palm pollen grain extract for 12 days. Then, the effect of date palm pollen grain on follicular growth and maturation were analyzed. Results: There was a significant increase in follicle growth and maturation rate in all treated groups as compared to the control group, but maturation rate was significantly higher in the presence of 20 μg/ml palm pollen grain. Conclusion: Supplementation of IVM media with date palm pollen grain extract improves the IVM of follicles.